GreenLab: un approccio green nel laboratorio di chimica organica - Burato, Andrea; Recchia, Silvia; Stazi, Federica (Chimica nella Scuola, 2025)
The organic chemistry lab in schools, traditionally characterized by use of hazardous reagents and toxic solvents, represents an environment where exposure to harmful substances can be frequent, both for students and teachers. Therefore, one of the most significant challenges facing this discipline today concerns the application of Green Chemistry principles, with the aim of making the laboratory a safer and more sustainable place. Making a teaching laboratory greener, especially one focused on organic chemistry, can represent a true revolution encompassing many aspects: from the use of less hazardous substances to the reduction of waste, from employing sustainable solvents to optimizing resources. The challenge lies in transforming traditional teaching methods, often long-standing, into practices that not only maintain educational effectiveness but also adhere to safety and sustainability standards. This article aims to explore the possibilities of applying Green Chemistry in school laboratory activities, providing concrete examples and emphasizing the importance of a responsible and conscious approach in training future chemistry professionals.